Water Supply and Sanitation for All - Paris, Stefania; Wang, S; Cross, Piers; Wilderer, A.; A. Middleton, R.; Armon, Robert; Cheruti, Uta; Price, Roland; Xiao, Lihua; Hubereter, Hans; Coombes, Yolande; Fayer, Ronald (IWA Publishing, 2007)
"The supply of healthy drinking water and disposal of our wastewater is a central problem. Solving this problem is one of the claims of the UN Millennium Development Goals, and consequently an obligation for all those involved with water to join efforts in finding solutions. Climate change, population growth, migration and urban sprawl are factors forcing us to reconsider the traditional approach to urban water management. The water supply and sanitation infrastructure currently in use worldwide was developed in and for countries which are relatively wealthy, and which have access to plenty of water. Is it really wise to build the same kind of infrastructure and to apply the same methods and processes in regions with different climatic, ecological and economical conditions? Should we maintain our flush and discharge sanitation concepts while freshwater is becoming a limited resource? Aren't there smarter more environmentally sound methods to use and safegaurd our precious water resources? Are water authorities, city planners, architects, regulators and politicians ready to accept innovative solutions deviating from those described in textbooks? Questions like these were raised during the International Symposium Water Supply and Sanitation for All held in Berching, Germany from September 27 - 28, 2007. This book collects the papers presented at this conference."